A föderalizmus pozíciói a Nagy Háború korában : Friedrich Naumann „Középeurópá”-ja száz év távlatából - Gyarmati, Enikő (Közép-Európai Közlemények, 2017)
Friedrich Naumann’s famous political essay about his Middle Europe concept, published in 1915 had been regarded highly controversial through the last hundred years. His study was translated into Hungary very soon in 1916 and inspired heated discussions about the future of the covenant between the German Empire and the Habsburg Monarchy. On the centenary of the Great War the present study’s intention is first to overview the international historiography of this question. According to the main conclusion of this overview the picture of an imperialistic concept of Naumann’s Middle Europe can absolutely be called into doubt. Secondly, in the light of the debate, organised by the Society for Social Sciences between February and April 1916 in Budapest this work also highlights the many pro’s and con’s formulated in the course of the exchange of the ideas. According to our evaluation Naumann’s most famous work had not been rejected uni sono in Hungary. Last but not least with a new reconstruction of the concept’s main ideas this study comes to the conclusion that Naumann had put forward a pladoyer for a custom union between the German Empire and Austria–Hungary in the second year of the Great War.